2021
DOI: 10.1017/s0007114521003007
|View full text |Cite
|
Sign up to set email alerts
|

Dietary and serum n-3 PUFA and polycystic ovary syndrome: a matched case–control study

Abstract: The results of epidemiological studies involving omega-3 polyunsaturated fatty acids (PUFAs) and polycystic ovary syndrome (PCOS) are scarce. This matched case-control study assessed the associations between omega-3 PUFAs and PCOS prevalence in 325 pairs of PCOS cases and healthy controls. Dietary information was assessed using a 102-item food frequency questionnaire. Fatty acids in serum phospholipids were measured with a gas chromatography method. We found that omega-3 PUFAs in serum phospholipids were inver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 45 publications
2
8
0
Order By: Relevance
“…In this study, we found that the levels of total MUFAs and PUFAs in the PCOS group were lower than those in the control group, whereas the levels of SFAs and TFAs were higher in the PCOS group. Consistent with our study, Li et al and Lu et al found that PCOS patients had decreased PUFA levels and increased levels of SFAs in serum compared to lean controls (18,19). In the subcutaneous adipose tissue of pregnant women with PCOS, the level of total PUFAs was lower, while that of total MUFAs was higher than that in non-PCOS women.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In this study, we found that the levels of total MUFAs and PUFAs in the PCOS group were lower than those in the control group, whereas the levels of SFAs and TFAs were higher in the PCOS group. Consistent with our study, Li et al and Lu et al found that PCOS patients had decreased PUFA levels and increased levels of SFAs in serum compared to lean controls (18,19). In the subcutaneous adipose tissue of pregnant women with PCOS, the level of total PUFAs was lower, while that of total MUFAs was higher than that in non-PCOS women.…”
Section: Discussionsupporting
confidence: 91%
“…Consistent with our study, Mousa et al found that lower DHA concentrations were associated with lower SHBG and higher adiposity, IR, Ins0, and FAI (17). Lu et al found that serum DHA levels were positively correlated with FSH and SHBG but negatively correlated with Ins0andtotal testosterone (19). In addition, DHA is one of the most well-known omega-3 PUFAs (n-3 PUFAs), and several studies have evaluated the changes in hormones in women with PCOS after supplementation with n-3PUFA; however, the results have been mixed.…”
Section: Discussionsupporting
confidence: 91%
“…The inconsistent results between dietary and circulating omega-3 PUFAs may be attributable to the difference in concentration in omega-3 PUFA concentrations in the dietary and serum phospholipids ( 38 ). Because gastrointestinal digestion and the absorption process of foods could affect the bioavailability and clinical efficacy of dietary omega-3 PUFAs, leading to the underestimation of their beneficial effects ( 24 ). Furthermore, not only genetic factors could influence the molecular response to different sources of omega-3 PUFAs, but also epigenetic modifications could obscure the clinical benefits of omega-3 PUFAs ( 24 ).…”
Section: Discussionmentioning
confidence: 99%
“…Potentially eligible patients who suffered PCOS were consecutively recruited from the Department of Gynecology, the First Affiliated Hospital of Chengdu Medical College in China. The detailed information on the study design has been described in a previous publication ( 24 ).…”
Section: Methodsmentioning
confidence: 99%
“…In women with polycystic ovary syndrome (PCOS), which is a vital factor of infertility, previous studies found that EPA and DHA may improve PCOS symptoms in rats by decreasing lipids and reducing weight and metabolic anomalies ( 42 ). A case-control study of Chinese women ( 43 ) also indicated the protective effects of consuming long-chain omega-3 PUFA, especially EPA and DHA, on PCOS. Nevertheless, according to our results, EPA and DPA may not be as efficient as expected in preventing infertility.…”
Section: Discussionmentioning
confidence: 99%